Currículo Digital, como estrategia para el desarrollo del pensamiento lógico matemático en los niños y niñas de 4 a 5 años en la Escuela General Juan Lavalle de la ciudad de Riobamba, durante el período lectivo 2019-2020 - Heredia Guamán, Marco Fernando (2019)
Logical mathematical thinking is a cognitive ability of every human being that must develop from its earliest years, but some children have problems to achieve it, which motivated to design a digital curriculum for the development of mathematical logical thinking in boys and girls 4 5 years from the General Juan Lavalle School during the period 2019-2020. The study was carried out under a quantitative approach, of an experimental type, since the variables were manipulated numerically, in the field, when searching for information in the General Juan Lavalle school, which has a population of 40 children from 4 to 5 years of Initial Education, as a small universe, the entire population was taken as the sample to apply the digital curriculum. In order to obtain data, the techniques of direct observation of the children in the classroom and the LAPD test were applied, with which they measured the level of skill and abilities of the mathematical logical thinking of the children of the School, before and after performing the activities indicated in the digital curriculum. Once the pretest and posttest data were analyzed in a free-use software, it was obtained as a result: in the pretest the children provided a very low level of mathematical logical thinking, which evidenced the need to apply the digital curriculum, after the application of the activities, the results of the post test indicated a significant improvement in the development of mathematical logical thinking. In conclusion: the application of the digital curriculum encourages the development of the mathematical logical thinking skills of the initial education boys and girls of the Juan Lavalle General School. Keywords: digital curriculum, development, mathematical logical thinking